Survey and analysis of factors that influence the occurrence of features on the left margin of a main erosive feature: Case of Cohab-16 in Bauru/SP - Souza, David Luan Mendes de; Romero , Letícia Marin; Furegatti, Simone Andrea (Technical and Scientific Journal Green Cities, 2021)
The increase in runoff due to the growing impermeability of cities, caused by the urbanization process, causes some harm and complications for society, such as floods and the appearance of linear erosions induced by the concentration of flow, in regions susceptible to erosive processes. The objective of the work presented here was to conduct a case study on the hydric erosion of the Edson Francisco da Silva Housing Nucleus, in the city of Bauru/SP, to identify the main influencing factors in the formation of erosive feature on the left margin of the main erosive feature and then, suggest possible ways to contain part of the surface runoff volume. Thus, the contribution area, the ramp length and the average slope were determined by the Google Earth software. While some of the characteristics of the studied erosive feature were obtained by consulting the Bauru urban erosion report, prepared by the Technological Research Institute and the Tietê-Jacaré watershed committee. And, the surface runoff calculation, the main focus of the study, was executed using the Rational Method. Some of the techniques presented to, as well as the conventional drainage system, reduce runoff are micro-reservoirs and infiltration trenches.KEYWORDS: Erosion, runoff, compensatory techniques.